Comparison of Retinal Changes Following Silicone Oil and Perfluoropropane Gas Tamponade for Proliferative Diabetic Retinopathy Patients - Wang, Tan; Wang, Erqian; Chen, Huan; Li, Ningning; Min, Hanyi (Frontiers in Physiology, 2022)
Purpose: To investigate the different tamponade effects of intravitreal silicone oil (SO) and perfluoropropane gas on the retinal structure and vasculature in proliferative diabetic retinopathy (PDR) patients. Methods: Thirty-eight eligible patients (47 eyes) with PDR requiring pars plana vitrectomy (PPV) were enrolled in the prospective observational study. Subjects were divided into two groups after PPV: SO group subjects underwent SO tamponade, whereas Gas group subjects underwent perfluoropropane gas tamponade. The primary outcomes of this study were longitudinal changes in retinal structure and vasculature between 10 days and 90 days after the operation. Secondary outcomes were longitudinal changes in pRNFL thickness between 10 and 90 days after the operation in each sector. Results: Thirty-six eyes of 27 patients with a median age of 56.6 ± 9.8 years completed follow-up and were statistically analyzed. No significant difference in demographics or clinical characteristics was found between the two groups. Eyes in the SO group had a statistically significant decrease in peripapillary retinal nerve fiber layer (pRNFL) thickness at 90 days after PPV (P<0.001), and there was a significant intergroup difference compared with the Gas group (P = 0.001), except for the temporal sector. Eyes in the Gas group had a statistically significant increase in parafoveal vessel density (VD) of the superficial vascular complex (SVC) at 90 days after PPV (P = 0.023), although there was no significant intergroup difference. The type of tamponade, changes in full retina thickness, and parafoveal SVC VD showed a significant correlation with changes in pRNFL thickness (all P<0.05). Conclusion: SO tamponade resulted in a significantly greater decrease in pRNFL over 90 days than gas tamponade in patients with PDR. In addition, the change in the pRNFL was significantly correlated with changes in full retina thickness and SVC VD after the operation.